2002
DOI: 10.1002/chir.10061
|View full text |Cite
|
Sign up to set email alerts
|

Alkylating agents from sugars: Synthesis of chlorambucil derivatives carried by chiral glycosyl glycerols derived from D‐Glucosamine

Abstract: Chlorambucilamide derivatives involving chiral glycosyl glycerols derived from D-glucosamine were synthesized in good yield by coupling the chlorambucil moiety to the amino group of omega-amino-(omega-1)-hydroxyalkyl 2-acylamino-4,6-O-benzylidene-2-deoxy-beta-D-glucopyranosides, and subsequent hydrolysis of the benzylidene group. The starting material was easily available from 2-acetamido-2-deoxy-D-glucose. The bonding of 2,3,4,6-tetra-O-pivaloyl-beta-D-galactopyranosylamine to chlorambucil by formation of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…The conjugation of sugars to therapeutic agents is not a new strategy and has already been successfully used to increase their selective delivery to highly metabolic targets [24][25][26][27][28][29]. In cancer therapeutics, studies aimed at increasing tumour selectivity using sugar derivatives as carriers have been conducted for many years, and several conjugated structures of established cytotoxics have been described [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…The conjugation of sugars to therapeutic agents is not a new strategy and has already been successfully used to increase their selective delivery to highly metabolic targets [24][25][26][27][28][29]. In cancer therapeutics, studies aimed at increasing tumour selectivity using sugar derivatives as carriers have been conducted for many years, and several conjugated structures of established cytotoxics have been described [25][26][27][28][29].…”
Section: Discussionmentioning
confidence: 99%
“…Our group has already described the use of this method for the synthesis of chiral epoxyalkyl glucosides with high diastereoisomeric excesses, 19 and derivatives of glycosylglycerol analogues that have been used as an alkylating agent carrier system. 23 The aim of this work was to obtain epoxyalkyl galactopyranosides and to study the influence of both the configuration of the sugar (galacto) and the role of the OH at the 2-and 3-position of the sugar on the stereoselectivity of the epoxidation reaction. In all cases the reaction was performed in chloroform at À15°C for the time necessary until plate detection showed that all the starting material had been consumed (for reaction conditions see Experimental).…”
Section: H Nmr)mentioning
confidence: 99%
“…The chiral epoxyalkyl glycosides, 19 epoxyamides 20 and epoxyacetals 21,22 obtained can be transformed into different types of compound. This method has enabled us to synthesise derivatives of glycosylglycerol analogues which have been used as an alkylating-agent carrier system 23 and phenylisoserine precursors 21,22 whose acetal function can be easily hydrolysed in the organism to separate the active fraction of the sugar moiety.…”
Section: Introductionmentioning
confidence: 99%
“…[5] In this sense we have used amino sugars as chiral templates in the stereoselective synthesis of diamino sugars, [6] chiral oxazolidines, [7] chiral oxiranes, [8] chiral cyclopropanes [9] and compounds with potential anticancer activity. [10] Glycal derivatives play an important role in carbohydrate chemistry as precursor compounds in the stereoselective synthesis of O-glycosides, [11] oligosaccharides, [12] S-glycosides, [13] 2-deoxynucleosides, [14] C-glycosides, [15] C-nucleo-tivity of these new 2-amino glycals with amines has been studied. The reactions were performed with two differently N-substituted amino glycals and a variety of alkyl-and arylamines.…”
Section: Introductionmentioning
confidence: 99%